2017
DOI: 10.1177/0310057x1704500208
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Month Evaluation of the Vivasight™ Video Double-Lumen Endotracheal Tube after Introduction into Thoracic Anaesthetic Practice at a Single Institution

Abstract: For a six-month period, all airway options used for non-emergent patients undergoing thoracic surgery requiring onelung ventilation at a single institution were assessed after introduction of the VivaSight™ double-lumen endotracheal tube (VivaSight-DL), a novel double-lumen tube with an integrated camera. This device displays a continuous view of the position of the tube relative to the carina. A total of 72 patients had lung separation with the VivaSight-DL. Lung separation was achieved on first attempt witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Another point emphasized by Liu et al is that CT-guided determination of the depth of LDLT insertion reduces the need for use of costly FOB to position a LDLT. 5,11,12 Although the data presented by Liu et al are significant, the small size of the study prevents extrapolation of the findings to all patients, namely obese patients (body mass index 4 35 kg/m 2 ), elderly (4 70 years old), and patients in American Society of Anesthesiologists functional class III or higher. 5 Even though FOB is costly, the reliability, safety, and efficacy of DLT placement when guidance with FOB is used are immense, and FOB is considered standard of care in both DLT placement and management of OLV should problems be encountered.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Another point emphasized by Liu et al is that CT-guided determination of the depth of LDLT insertion reduces the need for use of costly FOB to position a LDLT. 5,11,12 Although the data presented by Liu et al are significant, the small size of the study prevents extrapolation of the findings to all patients, namely obese patients (body mass index 4 35 kg/m 2 ), elderly (4 70 years old), and patients in American Society of Anesthesiologists functional class III or higher. 5 Even though FOB is costly, the reliability, safety, and efficacy of DLT placement when guidance with FOB is used are immense, and FOB is considered standard of care in both DLT placement and management of OLV should problems be encountered.…”
mentioning
confidence: 91%
“…The need for FOB guidance for confirming proper LDLT placement, however, may be eliminated with the novel Viva-Sight video LDLT, which has a high-resolution camera and a light source embedded on the medial aspect of the distal end of the tracheal lumen and enables accurate placement and continuous video monitoring of LDLT position on an external monitor. [7][8][9][10][11][12] Multiple studies have reported the VivaSight LDLT to be associated with shorter intubation and positioning times compared with the conventional LDLT because FOB is not required. [7][8][9][10][11][12] Moreover, because the VivaSight LDLT provides continuous surveillance, migration of a LDLT during surgery would be rapidly recognized and corrected without the need for FOB and may prevent complications associated with conventional LDLT.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent article describing a 6-month prospective experience in 72 patients with the VDLT in Australia, only 4% of patients with a VDLT required the use of an FOB to reposition the device intraoperatively. 7 Unfortunately, the result and primary outcome of this study seemed to be entirely self-evident because the method used by the members of the study team for placement and confirmation of a standard DLT required the use of an FOB 100% of the time. This created a perfunctory power analysis to justify a larger number of patients than seems necessary to draw the summary conclusion made by the investigators.…”
mentioning
confidence: 94%